Determinants of leverage: an analysis of consumer firms listed in KLSE / Wan Nur Syahizan Wan Ishak - Wan Ishak, Wan Nur Syahizan (2010)
The purpose of this research is to study the level of leverage of consumer firms. 20 consumer firms which listed in KLSE have been chosen as the in this study. The determinants of leverage are tangibility, growth, and size. The instrument of this study is case study form. The sampling has been done probability sampling. The data was analyzed using SPSS Students version 11 for windows programs. Reliability statistic is used to measure the goodness of questionnaire being used. Descriptive statistic in terms of mean and frequency is used to analyze the determinants of leverage of consumer firms. The inference statistic that is t- test and multiple regression analysis is used to test the hypothesis. The result shows that there is a positive linear correlation between size and leverage. For growth, it shows that there is a lower positive correlation with level of leverage. The result also shows that tangibility and leverage has a weak negative correlation.